Analisis Pengaruh Kualitas Produk, Harga dan Promosi Tehadap Keputusan Pembelian Handphone Merek Samsung (Studi Kasus Mahasiswa Universitas Muhammadiyah Surakarta) - Anggarisma, Galih; , Wafiatun Mukharomah, Dra., M.M (2015)
The purpose of this research to analyze the quality of the product, price and promotion to the Samsung brand mobile phone purchasing decisions for students of Muhammadiyah University of Surakarta. The population in this study are all students of the Samsung mobile phone users in 2013 at the University of Muhammadiyah Surakarta, while samples in this study using simple random sampling technique with a sampling of 100 students from the existing population. Methods of data collection in this study using interviews and questionnaires. Test instrument used to test the feasibility of a statement of validity and reliability. For the method of data analysis in this study uses multiple linear analysis is reinforced by the data normality test, multicolinearity test, heteroscedasticity test and autocorrelation test, determination test, multiple linear regression, F test and t test results that show significant effect between the quality of the product ( X 1), price (X 2)and promotion (X3) on purchase decisions (Y) mobile phone brand Samsung. Keywords: Quality of product, price, promotion, purchase decision.